Analysis of Factors Affecting Response Time in the Management of Heart Attacks Based on Pecalang (Buleleng Skilled Ambulance Officers) - Made Martini; Aryawan (Babali Publisher, 2025)
Background: A heart attack is commonly caused by acute coronary syndrome, which may be asymptomatic yet lead to sudden cardiac arrest, particularly outside a hospital setting. Ambulance personnel serve as frontline responders in delivering lifesaving interventions. This study analyzed the factors influencing ambulance response time in heart attack cases in Buleleng. Methods: A mixed-method design was applied in Buleleng Regency, simultaneously integrating quantitative and qualitative strands. This study involved 110 ambulance officers selected purposively from hospitals and community health centers across Buleleng. The qualitative strands involved 10 key informants. Quantitative variables included personnel experience, training, travel time, type of ambulance, and communication delay. Data were collected using structured questionnaires and complemented by interviews and FGDs for qualitative insights. Quantitative data were analyzed using correlation and regression tests, while qualitative data were thematically analyzed. Results: Personnel experience (r = –0.197; p = 0.039) significantly reduced response times, highlighting the importance of clinical competence acquired in the field. Training (r = 0.104; p = 0.278) enhanced service quality but showed limited direct impact without continuous practice and operational support. Travel time (r = 0.672; p < 0.001) emerged as the primary delay factor, influenced by distance, traffic, and road conditions. Type of ambulance (r = –0.235; p = 0.014) also affected mobilization efficiency, while communication barriers (r = 0.844; p < 0.001; OR = 0.002) were the strongest determinant of delays. Conclusion: Reducing ambulance response times requires systemic improvements in communication, fleet readiness, operational management, and infrastructure, beyond individual competence alone.